Analysis of CBSE Question Papers at the Higher Secondary Stage for the Years 2012 to 2014 (Mathematics) - Wazalwar, A.K. (SCHOOL SCIENCE, 2014)
It has been realised that education is the primary vehicle of upward economic mobility. This can be seen from the fact that, due to the pioneering entrepreneurial efforts of a few, India today is uniquely poised to become an intellectual powerhouse in the new ‘knowledge’ era. The areas of pharmaceuticals and biotech research, consulting and software development, promise hundreds of thousands of high-paying and fulfilling jobs—if, however, the Indian education system can produce students with the required skill-sets and attitudes. This is an immense challenge that the Indian education system faces, and needs to be tackled with fresh thinking. The conservative mentality that apparently seems to be progressive but has actually been colonial, needs to be discarded. The education system has the potential to create problem-solvers and rigorous thinkers. A lot of solutions for India’s complex social problems will need to come from creative visionaries working singly and collectively.